Implementasi Stimulasi Seni Pada Kurikulum Merdeka Di Tk Aba An-Nur - Neti, Neti Riana; Ertati, Ertati; Aprilina, Sandra; Parera, Siti Fatimah (STAI Bumi Silampari, 2024)
Art learning, especially in art education learning in kindergarten, where the teacher may not demand that children must become artists, but that is a teacher can motivate children so that art education is a means that can be used for development and self-knowledge. as well as being able to explore and develop children's creativity and skills such as in the form of a work of art. With this fine arts education, it can make children not only become artists but can educate children to be creative. Curriculum is the soul of the educational path. Education in Indonesia always experiences curriculum changes from time to time. Curriculum changes are of course unavoidable and unavoidable, but they must always be lived and adapted to needs as well as principles. In the world of education, curriculum changes are common, but implementation is not always easy to understand, especially for educators who are at the forefront of implementing the curriculum. Free drawing can stimulate children's imagination and bring out ideas that cause pleasure in the child. Through singing activities that are carried out every day, children can explore themselves in various tones, rhythms, imagination with movement, drama, discover new vocabulary and activities that stimulate artistic development. The development of dance art material adapted to the theme and was synchronized with extra teachers, singing and dancing. Based on the results of direct observations that have been made by the author on the implementation of dance learning in developing gross motor skills in early childhood.